Contextual sound preservation of selected local string instruments - Musib, Ahmad Faudzi (2015)
This thesis aims at approaches to audio field recording that forms contextual sound preservation under present-day conditions of wide-spread electro-acoustic enforcement applied on musical instruments, which were traditionally played in rural and/or communal settings in their special sound environments. Through the development of methods and technical possibilities, the study can contribute to high quality audio archiving that encompasses multiple sound perspectives. Thus it will help to preserve instrumental music in its sound context and document the unique relationship of the communities to it. The study is limited to a strict choice of instruments, which will play the role of a model for further applications. The study applies qualitative research methods, especially recording experiments leading to a descriptive analysis. From the fieldwork conducted, two selected local string instruments have been selected and recorded embedded in their actual sound context, namely the Bidayuh tube zither pratuokng and the sape native to various groups of the Kenyah and Kayan. Recordings were made from different positions utilizing appropriate audio recording equipment that is also examined in this study. The audio analysis focuses descriptively on the aspect of contextual sound preservation realized through recording instrumental sound from various highlighted positions. The sound captured represents four different perspectives, namely the sound of the immediate instrument, the ensemble in which it is played, the ensemble in its closer sound environment, and the entire sound setting in a place. The audio materials collected reveal that the sound context given in the rural and communal setting plays an important role for the community. For preservation purposes, the sound context cannot be eliminated or replaced even though it is a common practice in sound productions made in a conventional recording studio as this will affect the identification of instrumental sound and its perception. The importance of sound preservation with a possible choice of perception is not only limited to the chosen musical instruments. Contextual sound contributes to the overall information from the aspect of audio documentations and from the aspect of knowledge on music perception and communication. Based on the findings of the analysis, a few issues are discussed which include reviewing commercial recordings of local string instruments from the aspect of preservation and genre identity, instrumental sound modifications achieved acoustically through types and numbers of strings used, sizes and shapes; or electronically through installation of an electromagnetic pick-up, microphone techniques in live sound reinforcement, and cultural lexis. Through this, the importance of contextual sound preservation of the selected string instruments in their rural sound environment is informed. Further studies may focus on the application of the proposed recording concept with other musical instruments in Malaysia, namely in Sarawak, which may verify the applicability of the preservation method developed in this study.